Determinação de um novo valor para a entalpia de fusão do cristal perfeito de acetato de celulose - Cerqueira, Daniel Alves (2006)
The enthalpy of fusion of a perfect crystal of cellulose acetate was calculated in this thesis. In order to do so, cellulose samples from different sources were acetylated through the heterogenous acetilation methodology. The cellulose acetate samples were characterized by differencial scanning calorimetry (DSC) and by wide angle X-ray diffraction (WAXD). The X-ray diffractograms were deconvoluted into halos and peaks using the Pseudo-Voigt peak function of program Origin® 7.0. Two hypotheses were proposed in order to fit the deconvolution patterns into the two-phase model. In the first, the amorphous regions of the material was considered to be represented by the area of the halo located at 21º and the crystalline area by the maxima at 8º, 11º, 13º and 16º. In the second hypothesis, the amorphous region was considered to be represented by the areas of the maxima at 11º and 21º, and the crystalline region by the maxima at 8º, 13º and 16º. The WAXD crystallinities of the samples were then calculated from these values. The first hypothesis was ignored for presenting a very high crystallinity value for a sample that did not present an enthalpy of fusion. The second hypothesis was used, but the linear regression that defined the relationship between the enthalpy of fusion and the crystallinity of the materials was forced through zero. Through this relationship, the enthalpy of fusion of a perfect crystal of cellulose acetate was calculated to be 58.8 J/g.